1997
DOI: 10.1074/jbc.272.33.20811
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Multisubstrate Docking Protein Gab1 with the Hepatocyte Growth Factor Receptor Requires a Functional Grb2 Binding Site Involving Tyrosine 1356

Abstract: Hepatocyte growth factor/scatter factor is a multifunctional factor that induces mitogenesis, motility, invasion, and branching tubulogenesis of several epithelial and endothelial cell lines in culture. The receptor for hepatocyte growth factor has been identified as the Mettyrosine kinase. Upon stimulation with hepatocyte growth factor, the Met ␤ subunit becomes highly phosphorylated on tyrosine residues, one of which, tyrosine 1356 within the carboxyl terminus, is crucial for dissociation, motility, and bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 40 publications
6
183
1
Order By: Relevance
“…Moreover, PI3K activity is reported to be critical for Met-mediated cell migration, in vitro tubulogenesis (Derman et al, 1995), and resistance to apoptotic agents in MDA-MB-453 cells and in glioma cell lines (Bowers et al, 2000;Fan et al, 2000). The majority of activated PI3K downstream from the Met receptor is associated with the multisubstrate adaptor protein Gab-1 (Furge et al, 2000), whose recruitment and phosphorylation requires Y15 and, to a lesser extent, Y14 (Nguyen et al, 1997). Consistent with this, the Y14, 15FF mutation abolished the transforming activity of Met-SM in both the absence and presence of HGF/SF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PI3K activity is reported to be critical for Met-mediated cell migration, in vitro tubulogenesis (Derman et al, 1995), and resistance to apoptotic agents in MDA-MB-453 cells and in glioma cell lines (Bowers et al, 2000;Fan et al, 2000). The majority of activated PI3K downstream from the Met receptor is associated with the multisubstrate adaptor protein Gab-1 (Furge et al, 2000), whose recruitment and phosphorylation requires Y15 and, to a lesser extent, Y14 (Nguyen et al, 1997). Consistent with this, the Y14, 15FF mutation abolished the transforming activity of Met-SM in both the absence and presence of HGF/SF.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial cells, Gab1 is the major substrate for the Met RTK (Nguyen et al, 1997), and genetic and cell biological studies (Maroun et al, 1999;Maroun et al, 2000Maroun et al, , 2003 have demonstrated that Gab1 is crucial for the biological responses downstream from Met. Embryos nullizygous for Gab1 display all of the defects observed in Met or HGF/SF null embryos (Itoh et al, 2000;Sachs et al, 2000).…”
Section: Met Signal Transductionmentioning
confidence: 99%
“…Met signaling and Tpr ± Met mediated transformation are based on the activation of multiple pathways triggered by phosphorylation of two carboxy-terminal tyrosines (Y 1349 VHVNATY 1356 VNV, Ponzetto et al, 1993Ponzetto et al, , 1994Fixman et al, 1995). These tyrosine residues are part of a consensus sequence (YVH/NV) which mediates coupling of the receptor with several e ectors, including the Grb2/SoS complex (Ponzetto et al, 1994;Fixman et al, 1995), the p85 regulatory subunit of PI-3-kinase (Ponzetto et al, 1993), Stat-3 (Boccaccio et al, 1998), and the multiadaptor protein Gab1 (Weidner et al, 1996;Bardelli et al, 1997b;Nguyen et al, 1997). Grb2, in particular, requires an Asn in the +2 position for binding, and is thus linked to the receptor via the Y 1356 VNV motif Maina et al, 1996;Fixman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%